Analisis kompetensi strategis matematis mahasiswa dalam menyelesaikan masalah matematis ditinjau dari motivasi berprestasi - Ali, Ferdinandus Ardian; Jelatu, Silfanus; Murni, Viviana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research was conducted to find out what, why and how mathematical strategic abilities possessed by students. This research used qualitative methods. Research subjects were selected using purposive techniques, namely students who had high achievement motivation (MPT Subjects), students who had moderate achievement motivation (MPS Subjects), and students who had low achievement motivation (MPR Subjects). The main research instrument is the researcher himself, while the supporting instruments are tests and interview guidelines. Data collection is done by giving written tests on statistical material and conducting in-depth interviews. Research data was analyzed in the following ways, namely reducing data, presenting data, and drawing conclusions or verification. The results of the research show that MPT Subjects have good mathematical strategic abilities so they can solve mathematical problems correctly. Furthermore, MPS Subjects have mathematical strategic abilities but are still inadequate so that the mathematical problems they solve still contain errors, while MPR Subjects do not yet have good mathematical strategic abilities. well so it can't solve mathematical problems correctly.